Conflict-of-interest, copyright and other declarations - Peh, W.C.G.; Ng, K.H. (Singapore Medical Assoc, 2010)
Declarations of exclusive publication, author contribution, conflict-of-interest and copyright transfer are important formalities required by most biomedical journals. Conflict-of-interest may be personal, commercial, political, academic or financial. It is particularly important for authors to provide a full and complete disclosure of any financial relationship with a commercial organisation that may have an interest in the contents of the submitted manuscript. Editors, editorial board members and reviewers should also declare any possible conflicts-of-interest. The handling of conflict-of-interest during manuscript preparation, peer review and editorial decision-making impacts the credibility of published articles and scientific research in general.